1967
DOI: 10.2307/2694660
|View full text |Cite
|
Sign up to set email alerts
|

Stature at Tikal, Guatemala: Implications for Ancient Maya Demography and Social Organization

Abstract: This paper presents an analysis of stature of the prehistoric population from the Maya site of Tikal, Guatemala. From this analysis, based on 55 skeletons from the Tikal burial series, three important conclusions emerge with respect to ancient Maya demography and social organization. (1) Tikal was settled by people of moderate stature, and this remained relatively stable over several centuries. A marked reduction in male stature in Late Classic times may be indicative of a situation of nutritional stress, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(48 citation statements)
references
References 6 publications
(2 reference statements)
0
47
0
1
Order By: Relevance
“…Adult stature reflects, among other things, exposure to chronic stress during development (Haviland, 1967;Powell, 1988;Steckel, 1995;Roberts and Manchester, 2005). Children who are malnourished or fighting infection and disease must expend energy resources toward basic tissue maintenance and the immune response, diverting energy from growth and development to these essential metabolic functions.…”
Section: Pathological Conditionsmentioning
confidence: 99%
“…Adult stature reflects, among other things, exposure to chronic stress during development (Haviland, 1967;Powell, 1988;Steckel, 1995;Roberts and Manchester, 2005). Children who are malnourished or fighting infection and disease must expend energy resources toward basic tissue maintenance and the immune response, diverting energy from growth and development to these essential metabolic functions.…”
Section: Pathological Conditionsmentioning
confidence: 99%
“…A number of studies have suggested that prehistoric and historic elites were taller, better fed, or healthier than their poorer compatriots (Angel, 1984;Borgognini Tarli et al, 1992;Cohen, 1989;Hatch and Willey, 1974;Haviland, 1967;Rose, 1985;Schoeninger, 1979). However, other studies have shown that elites and commoners often did not differ skeletally (e.g., White et al, 1993;Wilkinson and Norelli, 1981).…”
mentioning
confidence: 99%
“…Statures were estimated from the reported long bone lengths from Zaculeu (Stewart, 1953) and from the Altar de Sacrificios (Saul, 1972) using the procedures of Genoves (1966Genoves ( ,1967 in the same manner as that used for the Oaxaca materials. The estimated statures for the Tikal sample (Haviland, 1967) (Saul, 1972). We grouped the materials from the Early, Late and Post Classic to more or less approximate the time interval of the Oaxaca Classic.…”
Section: Resultsmentioning
confidence: 99%